Managing the IT millennials - HR imperatives and interventions. (2016) - Shah, Hardik; Singh, Anup
The millennials (Generation Y or Gen Y) in India are a distinct and unique working group. They are highly ambitious, optimistic and have an extremely clear sense of where they want to reach. In India, for the next 30 years, Gen Y will be the largest percentage of employed workforce as half (approx.) of Indian population is under the age of 25 years. Millennials are bringing newer perspectives and challenges at the workplace with their new ways of contemplating work that are significantly different owing to their varying career aspirations, changing values, and motivators. Many companies are struggling to understand their career aspiration and motivators to design effective ways to manage them and to engage them actively. This study explored the career aspirations and motivation factors of millennials who are working in the IT sector. The primary data were collected using questionnaire survey and four rounds of focused group discussions (FGDs). The data generated insights into their aspirations, motivators, and engagement drivers. Based on the analysis, various HR interventions were suggested to attract, motivate and engage millennials continuously.